The relationship between well-being, mental health, and happiness among primary school teachers in Johor Bahru - Sagar, Sattiyan Nayar (2021)
Well-being is an important factor which indicates about our life quality. Good working conditions promote positive well-being among primary school teachers. Teachers’ well-being is the major influencing factor of dependent variables such mental health and happiness of teachers in school. The gap that exists between well- being, mental health and happiness of teachers need to be studied. Therefore, the main objective of this is set to discover the relationship between well-being, mental health and happiness of the primary school teachers. The population of this study are the 375 primary school teachers from Johor Bahru district selected using random sampling. Descriptive analysis showed that the level of well-being, mental health and happiness were average. Based on the analysis using Spearman’s correlation test, findings showed that there were significant relationships between primary school teachers’ well-being and mental health. Spearman’s correlation test showed that were significant relationships between primary schools’ teachers’ well-being and happiness. Overall, primary school teachers’ well-being contributes to affecting their mental health and happiness.